A review on the conventional, non-conventional, and hybrid micromachining of glass. Issue 2 (4th March 2019) - Jahan, Muhammad Pervej; Perveen, Asma; Rumsey, Ann M.
Abstract: Glass, commonly known as a brittle material, has the potential to be used in many applications in semiconductor, biomedical, mold manufacturing, opto-electronics, automobile and aerospace industries due to its superior mechanical strength and excellent wear and thermal resistance. This review article aims to present a comprehensive overview on the micromachining of difficult-to-cut glass materials. The article includes the state-of-the-art reviews on conventional, non-conventional and hybrid machining of various types of glass materials at micro-scale. A comparative analysis of various conventional and non-conventional micromachining processes used for machining glass is presented. Discussions on the current research trends and challenges in micromachining of glass have been included. Finally, recommendation for future research in the areas of glass micromachining has been provided.